THE ROLE OF ENGLISH LINGUISTIC COMPETENCE IN DEVELOPING CRITICAL THINKING, EMPATHY,AND PSYCHOLOGICAL WELL-BEING THROUGH EDUCATION (Contemporary Journal of Social Science Review, 2025)
The study is an exploration on the transformational effects of English linguistic competence on critical thinking, empathy and psychological well-being among college students in Gujranwala Division, Pakistan. By applying a mixed-methods research design, the research combined the quantitative surveys and standardized psychometric tests (n=188) with the qualitative semi-structured interviews (n=27) to determine the cognitive and emotional aspects of language acquisition. The main aim was to identify the impact that the proficiency in any global lingua franca has on the capability of the students to analyze the complex information, comprehend different opinions, and preserve the emotional balance. Quantitative results indicated that there are strong positive correlations between the English proficiency and critical thinking (r = 0.65), empathy (r = 0.52) and psychological well-being (r = 0.58). More sophisticated proficient students always scored higher as compared to their counterparts in the Watson-G Laser Critical Thinking Appraisal and Interpersonal Reactivity Index. Qualitative data also emphasized these findings, with students saying that language expertise not only helped them to improve their analysis synthesis, but also increased their understanding of other cultures through exposure to a variety of material in the world and, finally, it helped them to feel much more confident and to have fewer fears about academic work. The researchers conclude that English education is a significant initiating factor in the holistic development of students, which has much more advantages than communicative value. This evidence indicates that there is an urgent need by the policy makers and curriculum developers to abandon grammar-based models in favor of holistic frameworks that promote cognitive and emotional intelligence. With these wider developmental consequences at the forefront, educational institutions can now equip students in a more effective manner as they proceed to the intellectual and social challenges of an increasingly interconnected world more effectively in a resilient and knowledgeable way.